The cortical scene processing network emerges in infancy, prior to independent navigation experience - Frederik S. Kamps; Emily M. Chen; Haoyu Du; Heather L. Kosakowski; Ariel Fuchs; Nancy Kanwisher; Rebecca Saxe (Proceedings of the National Academy of Sciences, 2026)
Sighted people rely on vision to recognize and navigate the local environment. By adulthood, human cortex contains at least three regions that respond selectively to visual scene information, but it remains unknown when or how these regions develop. One hypothesis is that development of scene selectivity depends on passive exposure to the low-level visual statistics of scenes. Another hypothesis is that development depends on active experience using scene information to plan and guide navigation. Using ecological momentary assessment, we measured the quantity of forward-facing ego-motion and active navigation that infants experienced in the first months of life. By age 5 mo, infants cumulatively experienced around 340 h of forward facing ego-motion, almost exclusively passive. Next we used functional MRI in infants aged 2 to 9 mo to measure neural responses to scenes. Awake infants watched videos of ego-motion through real-world scenes, as well as videos of faces, objects, and scrambled videos. We found stronger responses to scenes than control conditions in the location of all three cortical scene regions. Responses in infant scene regions a) were dissociable from those in nearby face and object regions; b) could not be fully explained by low-level visual features; and c) were found even in subsamples of infants with no locomotor experience. Thus, the basic signature of scene selectivity emerges prior to independent navigation and with limited passive visual exposure to the diagnostic visual statistics of scenes.